Oxidative Desulfurization of Kerosene in Batch Reactor using Magnetite Mesoporous Silica Composite Zeolite Catalyst - Hussein, Ahmed K.; Al-Tabbakh, Ban A.; Jarullah, Aysar T. (Journal of Petroleum Research and Studies, 2024)
The petroleum refining sector has increasingly prioritized the creation of clean fuel as a crucial priority. The objective of this project is to generate environmentally friendly fuel through the use of a straightforward and uncomplicated method. Using a novel synthetic nano-catalyst, batch oxidative desulfurization (ODS) eliminates sulfur compounds in Kerosene. The new Catalyst's silica nano-particle support is initially manufactured utilizing the sol-gel technique. Subsequently, the support is employed to fabricate a synthetic composite nano-catalyst composed of ferric oxide, utilizing the techniques devised for extracting a novel synthetic handcrafted (Fe2O3/composite support) Nano-catalyst. The composite supports used for the robust studies on the desulfurization process contain different levels of HY-zeolite (100 percent Nano silica). These levels include 10% HY-zeolite + 90% Nano silica, 20% HY-zeolite + 80% Nano silica, and 30% HY-zeolite + 70% Nano silica. The supports and manufactured Catalyst underwent characterization tests, including SEM, XRD, XRF, TGA, FTIR, BET, and particle size distribution. The tests showed an ideal distribution of the active metal (Fe), different surface structures, and a high active metal dispersion were achieved. The prominent locations are identified as limited in number, and the catalysts exhibit metal-support solid interaction. The existing Catalyst's performance was evaluated using a batch reactor. The assessment involved testing the Catalyst at different reaction temperatures (303 to 393 K) and batch times (30 to 120 minutes) while varying HY-zeolite quantities in the composite supports.